Pelatihan Pembuatan Pakan Fermentasi di Desa Muaradua Kabupaten Sukabumi - Anna Vipta Resti Mauludyani; Wildan Nur Arrasyid Sane Pratinda; Ama Muhamad Ramdan; Anton Maulana Yusuf; Irna Ipangka; Moh. Syahrizal Sulaeman; Reza Maulana; Sarah Sofiah Azhar; Susi Lestari; Ujang Supiandi; Victor Hendrico Palisu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Muaradua Village is one of the villages in Kadudampit Subdistrict, Sukabumi District, with most of the people have their livelihoods on agriculture and livestock. The current problem in the livestock system in Muaradua Village was that there are still many breeders who only use weeds as animal feed. IPB students introduced an alternative forage to increase its shelf life as well as its nutrient content by developing fermented feed. The training, which was held in Kampung Legok Nyenang, Muaradua Village, started with dissemination, followed by practice of development of fermented feed (silage) and evaluation. There were 15 breeders and prospective breeders joined the training. Developed fermented rice straw has better quality than grass, seen from the unchanged leaf color, fermented cassava-like smell, very limited number of mushrooms and still clear and somewhat dry texture. Keywords: feed processing, fermented feed, forage feed, rice straw, ruminants